2020
DOI: 10.1097/qai.0000000000002422
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Norepinephrine and Neurocognition in HIV and Methamphetamine Dependence

Abstract: Objective: HIV disease and methamphetamine (METH) dependence share overlapping mechanisms of neurotoxicity that preferentially compromise monoamine-rich frontostriatal circuitry. However, norepinephrine (NE) function is poorly understood in HIV and METH dependence. We evaluated associations between cerebrospinal fluid (CSF) NE and HIV, METH dependence, and neurocognition.Methods: Participants included 125 adults, stratified by HIV serostatus (HIV+/HIV-) and recent METH dependence (METH+/METH-), who underwent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…In HIV-1 Tg rats, therefore, the preponderance of dendritic spines on distal dendrites, which extend into layer I, supports alterations in neurotransmitter innervation and synaptic connectivity. Indeed, neurotransmitter systems, including the dopamine (for review, [ 77 ]), norepinephrine (e.g., [ 78 ]) and serotonin (e.g., [ 79 , 80 ]) systems, are dysregulated by HIV-1 viral protein exposure. Furthermore, the magnitude of the rightward shift in the distribution of dendritic spines along the apical dendrite progresses with age in HIV-1 Tg animals, supporting an age-related loss in neurotransmitter innervation and synaptic connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…In HIV-1 Tg rats, therefore, the preponderance of dendritic spines on distal dendrites, which extend into layer I, supports alterations in neurotransmitter innervation and synaptic connectivity. Indeed, neurotransmitter systems, including the dopamine (for review, [ 77 ]), norepinephrine (e.g., [ 78 ]) and serotonin (e.g., [ 79 , 80 ]) systems, are dysregulated by HIV-1 viral protein exposure. Furthermore, the magnitude of the rightward shift in the distribution of dendritic spines along the apical dendrite progresses with age in HIV-1 Tg animals, supporting an age-related loss in neurotransmitter innervation and synaptic connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study with 4000 PWH from the Strategies for Management of Antiretroviral Therapy study revealed cross-sectional inverse associations between heart rate variability with soluble markers of inflammation and coagulation (140). Bearing in mind that stimulants act primarily by altering the function of catecholamines, stimulants and HIV are independently associated with higher NE in cerebrospinal fluid and dysregulated systemic metabolism of tyrosine (an essential amino acid precursor for catecholamines) (141,142). Alterations in catecholamines could partially explain associations of stimulant use with greater immune activation, inflammation, HIV proviral DNA in immune cells, and immune exhaustion in PWH who are virally suppressed or undetectable (142)(143)(144)(145)(146).…”
Section: Neuroendocrine Signaling and The Microbiome-gut-brain Axismentioning
confidence: 99%
“…In addition, sleep disturbances may be an underlying neurobiological mechanism of depression. While one study found the highest prevalence of lifetime major depression disorder in HIV+/METH+ individuals [ 142 ], the other study established that METH use was a more important determinant of depression than HIV-1 status [ 143 ]. In mouse studies, brain-specific Tat expression led not only to reward deficits, a core symptom of depression, but also to increasing METH-induced reward sensitivity [ 144 , 145 ].…”
Section: Combined Effects Of Hiv-1 Infection and Methamphetamine Use On Neurocognitive Functioningmentioning
confidence: 99%